SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN KARYAWAN MENGGUNAKAN METODE SAW PADA CV. GREEN ADVERTISING - Rinianty Rinianty; Sukardi Sukardi (Universitas Raharja, 2018)
Green Advertising is one of the businesses engaged in typing and printing services. In supporting the future of the company needed quality human resources. The selection process of employee acceptance on Green Advertising is still done manually, sorting the file of applicants and then compare with the predefined criteria. This takes a long time to affect the efficiency of decision making. From these problems, then needed a sistem that can help the leadership of Green Advertising in the receipt of employees. In this research used decision support sistem using Simple Additive Weighting method with prototype development model. The Simple Additive Weighting method is a weighted sum method used to find the optimal alternative of a number of alternatives with certain criteria. The criteria used in the research of the employee selection decision support sistem are the last educational criteria, work experience, skill and completeness of the file. Result of research from Decision Support Support Sistem Employee use computerized sistem and manual sistemsprovide the same alternative options.